PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS GAME EDUKASI “MATH ADVENTURE” UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Amanda, Alif Dhanti; Prihatin, Titi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop an interactive multimedia in the form of an educational game titled Math Adventure to enhance elementary school students' learning motivation, particularly in mathematics subjects covering Pictogram and Bar Chart topics. The background of the study stems from the low learning motivation among students, which is attributed to conventional teaching methods and teachers' limited use of technology-based media. This research employs the Research and Development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The product was developed using Construct 2 software and validated by media and content experts before being tested on fourth-grade students at SD Negeri Krengseng 01. Validation results indicate that the media is highly suitable for use, with average validation scores of 4.78 for media and 4.46 for content, both classified as